KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN AKURASI SHOOTING PADA SISWA EKSTRAKURIKULER FUTSAL SMP NEGERI 2 BANGUN PURBA - Deni Kusuma; Riwaldi Putra; Lolia Manurizal (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
This study aimed to determine the contribution of leg muscle explosive power and eye–foot coordination to shooting accuracy in futsal extracurricular students of SMP Negeri 2 Bangun Purba. This research used a quantitative method with a correlational approach. The sample consisted of 12 students selected using a total sampling technique. The research instruments included the vertical jump test to measure leg muscle explosive power, the soccer wall volley test to measure eye–foot coordination, and a shooting accuracy test to measure shooting ability. Data were analyzed using normality tests, simple correlation, and multiple linear regression with the help of SPSS software. The results showed that leg muscle explosive power had a significant contribution to shooting accuracy with a significance value of 0.000 (<0.05). Eye–foot coordination also showed a significant contribution to shooting accuracy with a significance value of 0.028 (<0.05). Simultaneously, both variables contributed significantly to shooting accuracy with a coefficient of determination of 97.5%. Therefore, improving leg muscle explosive power and eye–foot coordination can support the improvement of shooting accuracy in futsal games